Local government performance as a mediator between institutional capacity and community welfare in Jambi Province - Sam, Iskandar; Haryadi, Haryadi; Rahayu, Sri; Putra, Wirmie Eka; Sumarni, Sumarni (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2026)
Fiscal decentralization is intended to improve community welfare by strengthening local governments' fiscal capacity, organizational characteristics, and bureaucratic human resources. However, the mechanisms through which these institutional factors influence welfare remain insufficiently understood. This study investigates the direct and indirect effects of regional financial conditions, government size, and State Civil Apparatus (ASN) conditions on community welfare through local government performance in the district and municipal governments of Jambi Province, Indonesia. The analysis is based on balanced panel data from 11 local governments covering the 2014–2024 period and employs Partial Least Squares Structural Equation Modeling (PLS-SEM) using WarpPLS 8.0. The results indicate that regional financial conditions negatively affect government performance but positively affect community welfare. Government size has no significant effect on government performance but negatively affects community welfare. In contrast, ASN conditions positively influence both government performance and community welfare. Government performance, however, neither significantly affects community welfare nor mediates the relationships between regional financial conditions, government size, ASN conditions, and community welfare. These findings suggest that fiscal capacity and ASN quality contribute to community welfare primarily through direct mechanisms rather than through formal administrative performance. The study contributes to the literature on fiscal decentralization, Public Financial Management Theory, and Public Value Theory by demonstrating that administrative performance alone is insufficient to translate institutional capacity into improved welfare outcomes. The findings further underscore the importance of strengthening expenditure quality, enhancing ASN professionalism, and adopting outcome-oriented performance management to maximize the welfare benefits of fiscal decentralization.